AN EXPERIMENTAL COMPARATIVE ANALYSIS FOR LASER ENGRAVING DEPTH OF CAST ACRYLIC AND BIRCH PLYWOOD USING LBM - Avinash D. Sapkal; Abhishek M. Waykule; Dnyaneshwar D. Pawar; Mahesh A. Wagh; Uzairahamad M. Qureshi (International Journal of Innovations in Engineering Research and Technology, 2022)
Laser beam machining (LBM) is one of the most widely used thermal energy based non-contact type advance machining process. The laser beam machining process has various types of micro-machining applications such as laser cutting, fine cutting, laser drilling, micro-drilling, precision machining, micro-fabrication, laser marking, and engraving, etc. The cutting process is carried out by moving a focused laser beam along the surface of the workpiece with constant distance, thereby generating a narrow typically some tenths of a millimeter cut kerf. In recent years, researchers have explored a number of ways to improve the LBM process performance by analyzing different factors that affect the quality characteristics of the LBM process such as kerf width, kerf taper, surface finish, etc. It is seen from the literature that the process performance of the LBM process can be improved considerably by the appropriate selection of laser beam process parameters. Hence, in this work, an attempt is made for a comparative study of the LBM process for different materials using the experimental method. This will give the ready reference to the process planner to choose an appropriate set of optimum solutions as per requirement. For this work, the experiments are carried out on the CO2 laser machine for various materials. The process parameters considered are assisting gas pressure, cutting speed, laser power, and pulse frequency. The quality performance measures are in terms of engraving depth.